Ocular effects following aqueocentesis in dogs using variable needle sizes: fluorophotometric and tonometric evaluation - Allbaugh, Rachel A. (Kansas State University, 2009)
Objective – To measure blood aqueous-barrier breakdown following aqueocentesis using various needle sizes and to monitor the intraocular pressure (IOP) response. Animals – 24 healthy, adult dogs received treatment (24 treated eyes, 24 contralateral eyes); 3 dogs were untreated controls (6 control eyes). Procedures – Dogs receiving treatment were divided into 3 equal groups (25-, 27-, or 30- gauge needle aqueocentesis). In each dog the treated eye was determined randomly, the contralateral eye was untreated. Dogs that did not have aqueocentesis performed in either eye were used as controls. Aqueocentesis at the lateral limbus was performed under sedation and topical anesthesia. Anterior chamber fluorophotometry was performed before and after aqueocentesis on day 1. On days 2-5 sedation and fluorophotometry were repeated. Intraocular pressure was measured with a rebound tonometer at multiple time points. Results – Aqueocentesis resulted in blood-aqueous barrier breakdown in all treated eyes with barrier reestablishment present by day 5 detected by fluorophotometry. On day 2 the contralateral untreated eyes of all groups also showed statistically significant increased fluorescence (P < 0.05) following treatment of the opposite eye, but these values were not statistically significantly greater than untreated controls. In treated eyes there was no statistical difference in fluorescein concentration or IOP between 27- and 30-gauge needles. Use of the 25- gauge needle resulted in a statistically significant increase in anterior chamber fluorescence on days 3 and 5. It also caused a statistically significant increase in IOP 20 minutes following aqueocentesis as compared to the 27- and 30-gauge needles. Aside from this transient ocular hypertension, rapid resolution of ocular hypotony following aqueocentesis was observed in all treatment groups. Conclusions and Clinical Relevance – Aqueocentesis using a 25-gauge needle resulted in a greater degree of blood-aqueous barrier breakdown and a brief state of intraocular hypertension following paracentesis. Use of a 27- or 30-gauge needle is recommended for aqueous paracentesis. A consensual ocular reaction appeared to occur in dogs following unilateral traumatic blood-aqueous barrier breakdown and may be of clinical significance. Statistical significance was limited in this study due to high variability and large standard deviations.
Keywords: Blood-aqueous barrier; Consensual ocular reaction; Aqueous paracentesis; Fluorophotometry; Tonometry; Canine; Biology, Veterinary Science (0778); Health Sciences, Ophthalmology (0381)